Legal Frameworks and Bilateral Cooperation in Combating Human Trafficking on the Indonesia–Malaysia Border - Alif Oktavian; R. Dudy Heryadi; Wawan Budi Darmawan; Deasy Silvya Sari (Jurnal Hukum, 2026)
This research aims to examine human trafficking along the Indonesia–Malaysia border in Kalimantan and analyze how bilateral cooperation in border management addresses this issue. Using a qualitative descriptive approach within a normative legal framework, the study finds that human trafficking in Kalimantan is driven by several key factors, including geographic location, cultural ties, economic pressures, and government policies. Border areas such as Entikong, Aruk, and others are particularly vulnerable due to their proximity to Malaysia and strong cross-border ethnic connections. Economic factors, especially limited job opportunities in Kalimantan, push Indonesian migrant workers to seek employment in Malaysia, which offers better income and work options. Government policies, including ratification of international conventions and the establishment of a Task Force, face challenges in implementation. Effective handling of human trafficking requires strong cooperation between Indonesia and Malaysia, including joint patrols, intelligence sharing, joint training programs, collaboration with NGOs, and the development of operational protocols to strengthen border management and protect vulnerable populations.